The role of podcasts in shaping cultural awareness among the Jordanian public - Safori, Amjad (Frontiers in Communication, 2025)
IntroductionThe study aimed to explore the role of podcasts in enhancing cultural awareness among the Jordanian public. The study examines the cognitive, emotional, and behavioral aspects of following cultural topics through podcasts.MethodsThe present study employed a mixed-methods research design, integrating both quantitative and qualitative approaches to provide a comprehensive and nuanced understanding of the role of podcasts in shaping cultural awareness among the Jordanian public. The study population comprised Jordanian residents representing a range of age groups, educational levels, and geographical regions. The principal sample consisted of 498 participants, selected using quota sampling.ResultsA large percentage showed medium or high interest in podcasts, reflecting its growing role in transferring cultural knowledge. The results showed that providing rich and diverse content that meets the interests of listeners was a major factor in enhancing knowledge and awareness. Jordanians also benefited cognitively by learning about current events. Also, emotionally by enhancing cultural pride and changing negative attitudes, and behaviorally by encouraging knowledge exchange and adopting positive behaviors. The study proved the effect of podcasts as an educational and media tool that contributes to enhancing cultural understanding and community interaction.DiscussionThe study recommended developing the cultural content of podcasts and increasing interaction with the audience to maximize its impact and enhance its role in shaping an integrated cultural awareness in society.